Powder bed fusion 3D printing in precision manufacturing for biomedical applications: a comprehensive review - Joshua, Rajan John Nekin; Raj, Sakthivel Aravind; Hameed Sultan, Mohamed Thariq; Łukaszewicz, Andrzej; Józwik, Jerzy; Oksiuta, Zbigniew; Dziedzic, Krzysztof; Tofil, Arkadiusz; Shahar, Farah Syazwani (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Precision manufacturing requirements are the key to ensuring the quality and reliability of biomedical implants. The powder bed fusion (PBF) technique offers a promising solution, enabling the creation of complex, patient-specific implants with a high degree of precision. This technology is revolutionizing the biomedical industry, paving the way for a new era of personalized medicine. This review explores and details powder bed fusion 3D printing and its application in the biomedical field. It begins with an introduction to the powder bed fusion 3D-printing technology and its various classifications. Later, it analyzes the numerous fields in which powder bed fusion 3D printing has been successfully deployed where precision components are required, including the fabrication of personalized implants and scaffolds for tissue engineering. This review also discusses the potential advantages and limitations for using the powder bed fusion 3D-printing technology in terms of precision, customization, and cost effectiveness. In addition, it highlights the current challenges and prospects of the powder bed fusion 3D-printing technology. This work offers valuable insights for researchers engaged in the field, aiming to contribute to the advancement of the powder bed fusion 3D-printing technology in the context of precision manufacturing for biomedical applications.